Leadership across the globe / Vipin Gupta and Montgomery Van Wart with Paul Suino. - Gupta, Vipin, 1968-; Van Wart, Montgomery, 1951-; Suino, Paul (Routledge, 2016)
Generously illustrated with cases, boxed profiles, figures and examples from a wide range of organisations, this is a relevant resource for anyone seeking a leadership career on a global scale, in multinational enterprises, or in a multi-cultural context. Leadership Across the Globe aims to serve a growing interest in how to lead in a global or cross-cultural environment, and focuses on the corporate setting.